GROWTH, YIELD RESPONSES AND WATER RELATIONS OF DIFFERENT VARIETIES (OLEA EUROPAEA L.) CULTIVATED UNDER TWO WATER CONDITIONS IN SEMI-ARID CONDITIONS OF TUNISIA - Mouna, Aiachi Mezghani; Ali, Sahli; Naziha, Grati; Badii, Gaaliche; Ibtissem, Laaribi (European Scientific Journal, ESJ, 2014)
Water is the most important environmental constrain determining plant growth and fruit yield of olive tree plantations in arid region of Tunisia. A field experiment was carried out with the aim to study the behavior of local and foreigner varieties under climatic conditions of central Tunisia. Plants were planted in 2002 with a density of 204 tree ha-1. Trials were carried out over a 2-year period where two different irrigation treatments were applied (little water supply 10% ETc which was closed to rain-fed condition and full irrigated 100% ETc).Vegetative tree responses, as shoot growth and basal diameter, were evaluated. Morphological characteristics of leaves (leaf area, stomata density, number and diameter of the trichomes) and leaf water potential leaf were noted. Yield, fruit characteristics and oil quality indices were determined. The olive tree which received the total quantity of their water requirement, developed more important leaves, a higher stomata density and longer stomata pore. Seasonal dynamics of midday leaf water potential showed large variations over the season than those produced by the irrigation treatments. Then as the season progress, Î¨md decreased significantly during summer season, from June to September. Î¨md recovered quickly on the end of dry season when autumn rainfall arrived. Shoot elongation seems to be either affected by water status plant or its bearing conditions. Comparing the vegetative growth between 2008 (On year) and 2009 (Off year), it appeared that shoot growth was more important for non-bearing trees. Maximum productions recorded through the growing season (an On year followed by Off year) were given by Picholine, Coratina and Koroneiki irrigated with only 10% Etc which noted a biannual yield varying between 29 kg tree-1 (5919 kg ha-1) and 34 kg tree-1 (6936 kg ha-1). Chetoui showed the lowest biannual yield which not exceeds 8 kg tree- 1(1600 kg ha-1) even for trees which received 100% ETc. It showed poor adaptability in the south of Tunisia even under optimal conditions. Irrigation caused an increase of fruit weight and the pulp:stone ratio. From our results, it seems that water availability did not affect olive oil composition and oil fatty acid ratio.